Pengaruh Rebusan Daun Rami (Boehmeria Nivea) Terhadap Percepatan Penyembuhan Luka Jahitan Perinieum Pada Ibu Nifas - Anggie Nur'aini Ramadhani; Rifzul Maulina; Anik Purwati (Universitas Ivet, 2026)
Perineal sutures in postpartum mothers require proper care to prevent infection and promote faster wound healing. One complementary therapy that may be used is boiled ramie leaf (Boehmeria Nivea), as it contains bioactive compounds with anti-inflammatory and antibacterial properties. This study aimed to determine the effect of boiled ramie leaf (Boehmeria Nivea) on accelerating perineal suture wound healing among postpartum mothers at TPMB Ngadillah, Pakis District, Malang Regency. This research employed a quantitative approach using a quasi-experimental design with a non-equivalent control group design. The sample consisted of 32 postpartum mothers selected through purposive sampling and divided into an intervention group (n = 16) and a control group (n = 16). The findings showed that the mean REEDA score in the intervention group was 2.75, whereas the control group had a mean score of 6.88. The Mann-Whitney test yielded a p-value of less than 0.05, indicating a statistically significant effect of boiled ramie leaf administration on accelerating perineal suture wound healing. Therefore, boiled ramie leaf (Boehmeria Nivea) was proven to be effective in promoting faster healing of perineal sutures in postpartum mothers, as demonstrated by lower REEDA scores compared with the control group.